Perancangan Alat Penyambung Universal pada Transporter Mini Tandan Buah Segar Kelapa Sawit - Arkeman, Arlimda (MESIN, 2019)
Every palm oil plantation has different characteristics. In Indonesia, some of the palm oil plantations are unique because of its peaty, muddy, and bumpy features. Today, the existing Fresh Fruit Bunch (FFB) transport equipment is rigid and unable to follow the contour of outline of plantation ground, which limits its mobility. Therefore, it is necessary to design FFB transport equipment that offers ease of mobility. The new design has a universal joint feature that connects the front of part of the equipment (driver section) with the load carrier part (rear part). The design includes three-dimensional images with its simulations, two-dimensional images and the strength analysis of the joint. Both design drawings and strength analysis are carried out using SolidWorks engineering software. The result is a design of a universal joint with a dimension of 0.2 m in length and 0.15 m in width, and is capable of rotating in two directions; each at 30 degree on Y axis and 16 degree on X axis. All components of the universal joint are SS400 steel which has a tensile strength of 250 MPa. Calculation of strength with a tensile load of 1 ton results in a safety factor of 833. This safety factor ensures the maximum life span and strength of the universal joint.